What should be the characteristics of the ideal bone graft substitute?: Combining scaffolds with growth factors and/or stem cells - Janicki, Patricia; Schmidmaier, Gerhard (Injury, 2011)
Reconstruction of large bone defects or non-unions resulting from biochemical disorders, tumour resections or complicated fractures is still a challenge for orthopaedic and trauma surgery. On the one hand, autografts harbour most features of ideal bone graft substitutes but on the other hand, they have a lot insurmountable disadvantages. An ideal bone graft substitute should be biomechanically stable, able to degrade within an appropriate time frame, exhibit osteoconductive, osteogenic and osteoinductive properties and provide a favourable environment for invading blood vessels and bone forming cells. Whilst osteoconductivity of biomaterials for bone tissue engineering strategies can be directed by their composition, surface character and internal structure, osteoinductive and osteogenic features can be provided by growth factors originally participating in fracture healing and/or multipotent mesenchymal stromal/stem cells (MSC) capable of rebuilding bone and marrow structures. In this review, aspects of the clinical application of the most commonly used growth factors for bone repair, the bone morphogenetic proteins (BMPs), and the potential use of human MSC for clinical application will be discussed.
Gesehen am 04.07.2022